Rational behavior of self medication on the community of Cangkringan and Depok subdistrict of Sleman district - Kristina, Susi Ari; Prabandar, Yayi Suryo; Sudjaswadi, Riswaka (Indonesian Journal of Pharmacy, 2008)
Self-medication is defined as usage of drugs in community to relieve symptoms of minor illnesses without doctor intervention. Self-medication prevalence in Indonesia in 2004 is 24.1.% and in DIY province in 2005 is 87.73.%. The behavior of rational self-medication is probably influenced by sex, age, education level, occupation, income level, knowledge, and positive attitude toward self-medication. This was an observational research with cross sectional design. The number of respondent was 174, and the samples were chosen by multistage random sampling based on the villages number. Data was collected by using structured questionnaire and nonpartisipative observation. The data was analyzed by using independent sample t-test, Pearson correlation and multivariate analysis with multiple logistic regression.The result of the research showed that there was significant relationship between sex, age, level of knowledge, occupation, income level, knowledge and attitude with rational self-medication behavior. Multivariate analysis result showed that education level was themost influencing rational self-medication behavior at confidence level 95.%. There was significant relationship between knowledge, attitude, sex, age, level of knowledge, occupation and income level with rational self-medication behavior. Education level was the most influencing rational self-medication behavior.Key words: self-medication behavior, self-medication knowledge, self-medication attitude